2018. The Global Point Prevalence Survey of Antimicrobial Consumption and Resistance: Quantity and Quality of Antimicrobial Prescribing for Inpatients with Pneumonia in the Philippines in 2018 - De los Reyes, Mari Rose Aplasca (Open Forum Infect Dis, 2019)
BACKGROUND: Pneumonia is the most common indication for prescription of antibiotics in hospitals in the Philippines. We describe the quality and quantity of antibiotic prescribing for hospitalized pneumonia patients in the Philippines in 2018 (www.global-PPS.com). METHODS: A point prevalence survey was performed from September to December 2018 in 28 public and private hospitals in Luzon, Mindanao, and Visayas regions. Ward- and patient-level data were collected using a standardized methodology and entered through a web-based application. We analyzed all antibiotic (ATC J01) prescriptions for inpatients with pneumonia. RESULTS: Of all hospitalized patients, 16.2% (n = 1516) received one or more antibiotic (J01) for treatment of pneumonia, majority (78.3%) of which were for community-acquired pneumonia (CAP). In adults, the most commonly used antibiotics were azithromycin (19.5%), ceftriaxone (19.0%), and piperacillin/enzyme inhibitor (13.2%) for CAP and meropenem (19.8%), piperacillin/enzyme inhibitor (18.9%), and levofloxacin (8.6%) for healthcare-associated pneumonia (HAP). In neonates and children, cefuroxime was used most often (20.1%) for treatment of CAP, followed by ampicillin (16.7%) and amikacin (15.3%). Children and neonates with HAP were most commonly treated with amikacin (18.7%), meropenem (15.7%), and ampicillin (10.4%). Overall, 16.0% of all antibiotic prescriptions for pneumonia were based on microbiological results, 11.3% for CAP and 33.9% for HAP. Microbiology-based prescriptions were most commonly targeted at ESBL-producing Enterobacteriaceae (8.4%). Further analysis of quality indicators showed that up to 80.0% of all prescriptions for pneumonia were compliant to local guidelines and reason in notes was documented for 81.0% of prescriptions. However, the stop or review date of antibiotic treatment for pneumonia was less documented (27.8%). CONCLUSION: Global-PPS data provided valuable insights into the quantity and quality of antibiotic prescribing for pneumonia inpatients. These results will be fedback to the Department of Health, medical societies, and hospitals for prioritization of targets and policies toward the improvement of the Philippine antimicrobial stewardship program. DISCLOSURES: All authors: No reported disclosures.